Coupling between electromagnetic waves and wires using transmission-line modelling - Naylor, Phillip (1986)
Three techniques are used to introduce wire models into Transmission Line Matrix (TLM) Electromagnetic field solvers. The first involves the setting up of a one dimensional time-domain transmission-line model of a pair of wires. Voltages and currents coupled into the wires can be obtained from the incident fields. The differentials of these fields are used as source terms of the one dimensional model. Results obtained by this model were compared with frequency domain results and good agreement was found. Non-linear loads can easily be modelled, and the response of a simple non-linear device is presented.